Humerus Supracondylar Fracture in Children Treated with Closed Redution Percutaneous Cross Pinning vs Two Lateral Pinning - Fatima, Fatima Rauf, Sobia Nawaz, Muhammad Adeem Busharat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: With this research, we hope that we can compare the effectiveness of percutaneous cross pins in treating paediatric supracondylar humerus fractures to that of two-lateral pins. Study Design: Prospective study Place and Duration: Children Hospital Faisalabad/ Bahawal Victoria Hospital Bahawalpur.April 2018-Oct 2018. Methods: This research included 104 patients of both sexes. After permission, the patient’s age, sex, and BMI were recorded. The patients ranged in age from 3 to 10. Children with supracondylar humerus fractures were split into two groups. Percutaneous cross pinning was performed on group C patients, whereas two lateral pinning was done on group D patients. We examined the radiological and functional results and the occurrence of problems between the two groups. SPSS 21.0 was used to analyze the data. Results: In current study surgical time in group C was lower as compared to group D and had higher radiation time with p value <0.003. Post operatively frequency of excellent results in group C was higher among 35 (67.3%) cases as compared to group D in 27 (51.9%) patients. Frequency of poor results in group D was higher in 5 (9.6%) patients as compared to group C in 1 (1.9%) cases. Complication rate was also higher in group D 12 (23.1%) patients as compared to group C in only 6 (11.5%) cases. Conclusion: We observed that percutaneous pinning was more advantageous than two lateral pinnings in treating children with closed reduction supracondylar humerus fractures.